2015
DOI: 10.1002/2015wr017850
|View full text |Cite
|
Sign up to set email alerts
|

Annually resolved late Holocene paleohydrology of the southern Sierra Nevada and Tulare Lake, California

Abstract: Here we present 2000 year long, annually resolved records of streamflow for the Kings, Kaweah, Tule, and Kern Rivers in the southwestern Sierra Nevada of California and consequent lake-level fluctuations at Tulare Lake in the southern San Joaquin Valley. The integrated approach of using moisturesensitive tree ring records from the Living Blended Drought Atlas to reconstruct annual discharge and then routing this discharge to an annual Tulare Lake water balance model highlights the differences between these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…The approach to reconstructing CONUS streamflow is therefore based on the preservation of climate signals in tree‐rings used to reconstruct PDSI, which is then used to reconstruct streamflow (see flowchart of modeling approach in Figure ). While the direct use of moisture‐sensitive tree‐ring chronologies to reconstruct streamflow is more widespread, the approach of using PDSI is not entirely novel given previous attempts to reconstruct streamflow from drought indices [e.g., Graham and Hughes , ; Adams et al ., ; Coulthard et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…The approach to reconstructing CONUS streamflow is therefore based on the preservation of climate signals in tree‐rings used to reconstruct PDSI, which is then used to reconstruct streamflow (see flowchart of modeling approach in Figure ). While the direct use of moisture‐sensitive tree‐ring chronologies to reconstruct streamflow is more widespread, the approach of using PDSI is not entirely novel given previous attempts to reconstruct streamflow from drought indices [e.g., Graham and Hughes , ; Adams et al ., ; Coulthard et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Radiocarbon analysis of the charcoal yielded a date of 870 ±40 14C yr BP (910-700 cal yr BP) with a median probability age of 780 cal yr BP ( Table 1). The 14C age of ~ 780 cal yr BP provides direct evidence that water levels reached an elevation as high as 1103m in Owens Lake basin during a major wet interval during the Medieval Climate Anomaly (MCA) in the western Great Basin, known as the Intervening Pluvial (Cook et al, 2010) or Medieval Pluvial (Adams et al, 2015;Hatchett et al, 2015). The bristlecone pine tree-ring chronologies in the nearby White Mountains support a short period of extreme hydroclimate variability at this time with a 10-49 yr wet and anomalously cold interval centered at ~ 840 cal yr BP (Leavitt, 1994;Hughes and Graumlich, 1996;Cook et al, 2010;Bale et al, 2011;Salzer et al, 2014).…”
Section: Medieval Pluvial High Stand At 1103m (810-790 Cal Yr Bp)mentioning
confidence: 99%
“…Hydroclimate variability from tree-ring chronologies Numerous studies in the western United States and Sierra Nevada have developed tree-ring reconstructions to infer precipitation variability and drought, streamflow, lake-level fluctuations, and snow water equivalent (e.g., Cook et al, 1999Cook et al, , 2004Meko and Woodhouse, 2011;Graham and Hughes, 2007;Adams et al, 2015;Belmecheri et al, 2015). Figure 12.…”
Section: Late Holocene Hydroclimate Variabilitymentioning
confidence: 99%
“…Belmecheri et al [2016] used a tree ring-based reconstruction approach to estimate that the 1 April 2015 SWE had a return period of 3100 years. Finally, Adams et al [2015] found that, in terms of streamflow, the ongoing drought in the Southern Sierra Nevada was the driest continuous 4 year period over the last~2000 years.…”
Section: Introductionmentioning
confidence: 96%
“…Finally, Adams et al . [] found that, in terms of streamflow, the ongoing drought in the Southern Sierra Nevada was the driest continuous 4 year period over the last ~2000 years.…”
Section: Introductionmentioning
confidence: 99%